Geneva® Series Rootstocks for Apple Trees Under Extreme Replanting Conditions in Southern Brazil - Rufato, Leo; da Silva, Pricila Santos; Kretzschmar, Aike Anneliese; Bogo, Amauri; de Macedo, Tiago Afonso; Welter, Juliana Fátima; Fazio, Gennaro; Petry, Daiana (Frontiers in Plant Science, 2021)
Geneva® rootstocks in Brazil are known to be efficient in controlling vigor, and are precocious and resistant to diseases. The objective of this study was to evaluate the performance of apple tree cultivars grafted on the Geneva® rootstocks in severe replant disease areas, by planting 60 days after the eradication. The experiments were implemented in 2017, in São Joaquim and Vacaria. The Gala Select and Fuji Suprema cultivars were grafted onto ‘G.202’, ‘G.814’, ‘G.210’, and ‘G.213’ rootstocks in the Tall Spindle training system. In 2018/2019, total thinning was carried out to promote plant growth. In São Joaquim, partial thinning was carried out in 2019/2020 harvest of ‘Gala Select’. The rootstocks were divided into two groups based on vigor, for both areas and cultivars. ‘G.202’ and ‘G.213’ were 40% less vigorous than ‘G.210’ and ‘G.814’. For ‘Gala Select’, the extreme non-fallow condition mainly affected the vigor and productivity of ‘G.213’ in both areas. At the end of two harvests, ‘G.213’ was 17% less productive than ‘G.210’, contrary to what is observed in areas where the fallow period is respected. However, ‘G.213’ confirmed a greater yield efficiency, which was 27% higher than ‘G.210’. This suggests that a perspective of forecasting production for the third crop is higher for ‘G.213’ than for ‘G.210’. In the case of ‘Fuji Suprema’, the G.210 rootstock was the most productive in both areas. In São Joaquim, ‘G.202’ matched ‘G.210’ in productivity and efficiency as it sprouts better in colder regions. Considering the fruit quality, ‘G.213’ anticipated the maturation with fruits of larger size and higher total soluble solids (TSS) in both areas and cultivars, making it possible to anticipate the harvest. It was concluded that the non-fallow condition does not alter the relative differences in vigor and fruit quality among the rootstocks. However, notwithstanding the overall replant tolerance of these rootstocks, it does reduce productivity by mainly affecting less vigorous rootstocks that need about three crops to overcome the allelopathic effects of the soil and start growing normally. The G.210 semi-dwarfing rootstock is an alternative for the immediate conversion of apple orchards of Gala Select and Fuji Suprema cultivars in southern Brazil.